Proximity of posterior teeth to mandibular canal with 3D measurements in a population of western China - Lu Feng; Xi Zhao; Bo Zheng; Dingming Huang; Lan Zhang (PLoS ONE, 2026)
Objectives The mandibular canal (MC) is an important anatomical structure that sometimes incurs injuries. Complications, such as paresthesia, neuropathic pain, and numbness, usually occur and are challenging for patients and dentists to resolve. The relationship of the MC with mandibular posterior teeth is of great clinical importance to avoid damage. The aim of this study was to evaluate the proximity of adjacent teeth to the MC in a Western Chinese population using 3D reconstruction and measurements. Methods Cone-beam computed tomography (CBCT) images were collected in patients who met the inclusion and exclusion criteria. The 3D models of the MCs were reconstructed and imported to 3D viewing software. The root apices were identified precisely. The relative location of the MC and the shortest distance between the MC and root apex of each mandibular posterior tooth were measured in 3D. The age and sex of the patients, the tooth position, and whether the left or right mandible was affected were recorded. The relationships between distance and age, sex, mandible position and tooth position were analyzed using t-tests or analysis of variance (ANOVA). Results In total, 125 cone-beam computed tomography (CBCT) scans were performed. The average shortest distances from the MC to the mandibular teeth were 5.7463 ± 2.3089 mm (second premolar), 7.1025 ± 2.6063 mm (first molar) and 4.5082 ± 2.6199 mm (second molar). An occurrence rate of ≤1 mm between the root tips and the MC was found in 9.7%, 0.7% and 1.7% of the measured mandibular second and first molars and mandibular second premolars, respectively. The distances in the females were significantly shorter than those in the males in all tooth positions (P < 0.05). The distances from the MC to all roots of the mandibular second molar, distal root of the first molar, distal lingual root of the first molar or root of the second premolar were smaller in the 18- to 28-year-old group than in the other age groups (P < 0.05). No significant differences were found concerning the location (right/left mandible) of the teeth (P > 0.05). More than half of the mandibular second molars were located on the lingual side of the MC, while the mandibular first molars and second premolars were mostly located on the buccal side of the MC. Conclusions There is a strong relationship between the roots of the mandibular second molars and the MC in Western Chinese people. Distance is strongly related to sex and age. Therefore, clinicians should carefully consider these factors when performing preoperative examinations or surgical or endodontic procedures. The 3D reconstruction and measurements of CBCT images can be used to provide clinicians with a more accurate and comprehensive understanding of the relationships between the MC and adjacent structures.